Effect of Corporate Governance Attributes on Audit Quality in Nepalese Commercial Banks - Shrestha, Abhishek; Wagle, Bibek; Lama, Dipak (Nepalese Journal of Business, 2025)
The study examines the effect of corporate governance attributes on audit quality in Nepalese commercial banks. Audit committee and audit fee are the selected dependent variables. The selected independent variables are board size, board independence, female directors on board, institutional ownership, bank size, and no of meetings. The study is based on secondary data of 10 commercial banks with 100 observations for the period from 2013/14 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance attributes on audit quality in Nepalese commercial banks. The study showed that board size has a positive relationship with audit committee and audit fees. It indicates that increase in board size leads to increase in audit committee and audit fees. Similarly, board independence has a positive relationship with audit committee and audit fees. It indicates that higher the board independence, higher would be the audit committee and audit fees. Likewise, female director has a positive relationship with audit committee and audit fees. It indicates that presence of female director in the board leads to increase in audit committee and audit fees. Further, institutional ownership has a positive relationship with audit committee and audit fees. It indicates that increase in institutional ownership leads to increase in audit committee and audit fees. In addition, number of meetings have positive relationship with audit committee and audit fees. It indicates that higher the number of meetings, higher would be the audit committee and audit fees. Moreover, bank size has a positive relationship with audit committee and audit fees. It indicates that higher the bank size, higher would be the audit committee and audit fees.